Can Vitamin D Positively Impact Sarcopenia Severity Among Older Adults with Hand Osteoarthritis: A Review of the Evidence - Ray Marks (Journal of Aging Research And Healthcare, 2023)
Aim This review examines the research base concerning hand osteoarthritis and changes in muscle mass and quality known as sarcopenia and the possible use of vitamin-D supplementation for reducing this potentially adverse functionally disabling state. Methods Publications detailing a possible link between hand osteoarthritis manifestations and sarcopenia, plus those discussing vitamin D as a possible intervention strategy for minimizing sarcopenia in the older adult were systematically sought and reviewed. Results Collectively, data reveal hand osteoarthritis in the older population is common, and is possibly affected by age as well as disease associated muscle mass declines. Vitamin D, a powerful steroid required by the body to foster many life affirming physiological functions may help reduce the degree of any prevailing sarcopenia and thereby some degree of hand osteoarthritis disability. Conclusions Older individuals with hand osteoarthritis, as well as healthy older adults at risk for sarcopenia are likely to benefit physically from efforts to clarify the extent of this association and if indicated, to examine and intervene thoughtfully to maximize muscle composition as well as safe vitamin D levels where subnormal. Researchers can make highly notable impacts in multiple spheres in this regard and are encouraged to do so.
Keywords: Aging